Mother-child pass in Austria and primary toxoplasmosis infections in pregnant women - Moese, J R; Vander-Moese, A (Central European journal of public health, 1998)
The mother-child pass (MCP) in Austria, introduced in 1975, has been successful till now. The changes and the results of the serological screening for toxoplasmosis, included in the MCP over the last 22 years, are demonstrated.
Keywords: Female; Prevalence; vertikální přenos infekce; Toxoplasmosis; ženské pohlaví; lidé; parazitární komplikace těhotenství; Austria; těhotenství; plošný screening; prevalence; Maternal Health Services; prenatální péče; služby zdravotní péče o matku; Prenatal Care; toxoplazmóza; Mass Screening; Pregnancy; Infectious Disease Transmission, Vertical; Rakousko; Pregnancy Complications, Parasitic; Humans